1997
DOI: 10.1007/bf02895160
|View full text |Cite
|
Sign up to set email alerts
|

Pain in the obese: Impact on Health-Related Quality-of-Life

Abstract: Obesity is a major public health problem associated with increased health risks, chronic pain, and decrements in functional health status and subjective well-being. To examine the impact of pain on Health-Related Quality-of-Life (HRQL). 312 consecutive persons seeking medically-supervised weight loss treatment completed a sociodemographic questionnaire, the Medical Outcomes Study Short-Form Health Survey (SF-36), and underwent a series of clinical evaluations. Forty-eight percent of the patients when asked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
72
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 7 publications
10
72
0
3
Order By: Relevance
“…2,9,10,[13][14][15]37 We are also in agreement with others who have found that obese patients have lower levels of HRQL, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and that the estimated loss of HRQL associated with obesity is reduced (although not eliminated) when levels of co-morbidity are controlled for. [12][13][14][15] Similarly, others have also found that pre-obese individuals do not have a significantly lower HRQL than patients with a normal BMI after other factors are controlled for.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…2,9,10,[13][14][15]37 We are also in agreement with others who have found that obese patients have lower levels of HRQL, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and that the estimated loss of HRQL associated with obesity is reduced (although not eliminated) when levels of co-morbidity are controlled for. [12][13][14][15] Similarly, others have also found that pre-obese individuals do not have a significantly lower HRQL than patients with a normal BMI after other factors are controlled for.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] To our knowledge, only one study has shown that utility measures, which are designed to estimate and compare the benefits of many interventions on a common scale (where zero equals death and full health equals one), can detect the loss in HRQL associated with obesity. 15 The necessity for such utility measures is demonstrated by the fact that both the United States (US) Public Health Service Panel on Costeffectiveness in Health and Medicine and the United Kingdom (UK) National Institute for Health and Clinical Excellence (NICE) prefer utility measures to be used when assessing the cost-effectiveness of new, and current, interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation, whenever present, is limited to a few, but not all, physical aspects of obesity, namely Physical Functioning 13 or Bodily Pain. 31 This was also found in the present series, where Bodily Pain was the sole scale of SF-36 whose changes paralleled CBT-induced changes in BMI.…”
Section: Discussionsupporting
confidence: 87%
“…5,6 The higher fatigability suffered by obese subjects, which are constrained to carry more weight than lean individuals as a consequence of added inert fat mass, has been attributed to several different factors, including chronic physical inactivity, concomitant diseases and chronic pain, as well as poor selfesteem. [7][8][9] Nonetheless, it has been demonstrated that obese patients actually display major motor limitations due to a reduction of both aerobic and anaerobic capabilities, which can be evidenced with adequate functional motor tests suitable for this disabled condition. [10][11][12][13] While reductions in aerobic power interfere with the capability to sustain relatively intense and prolonged exercise, anaerobic power is related to the accomplishment of short and vigorous movements more directly involved in everyday life activities (ie rapidly climbing up a flair of stairs or running to catch a bus) or even in brisk postural adjustments to prevent falls and accidental crushes.…”
Section: Introductionmentioning
confidence: 99%